Institutions, infrastructure, and trade - Joseph F. Francois; Miriam Manchin (Johannes Kepler University of Linz, Department of Economics, 2007)
We work with a panel of bilateral trade flows from 1988 to 2002, exploring the influence of infrastructure, institutional quality, colonial and geographic context, and trade preferences on the pattern of bilateral trade. We are interested in threshold effects, and so emphasize those cases where bilateral country pairs do not actually trade. We depart from the institutions and infrastructure literature in this respect, using selection-based gravity modeling of trade flows. We also depart from this literature by mixing principal components (to condense our institutional and infrastructure measures) with a focus on deviations from expected values for given income cohorts to control for multicollinearity. Infrastructure, and institutional quality, are significant determinants not only of export levels, but also of the likelihood exports will take place at all. Our results support the notion that export performance, and the propensity to take part in the trading system at all, depends on institutional quality and access to well developed transport and communications infrastructure. Indeed, this dependence is far more important, empirically, than variations in tariffs in explaining sample variations in North-South trade. This implies that policy emphasis on developing country market access, instead of support for trade facilitation, may be misplaced.
Keywords: O19; F10; F15; 330; exports; trade; institutions; infrastructure; zero-trade; gravity model; Außenhandelsstruktur; Infrastruktur; Gravitationsmodell; Nord-Süd-Beziehungen; Welt